Effectiveness of Extension Methods for Knowledge and Skill Development - Singh, Dan; Yadav, R.N.; Singh, D.K.; Singh, Gopal; Singh, Rajendra; Singh, Balvir (Indian Journal of Extension Education, 2018)
The present study was conducted in Saharanpur and Hapur districts of Western Uttar Pradesh to know the effectiveness of extension methods. The study reveals that before exposure of different extension methods, about 66.87 per cent vegetable growers had medium knowledge of vegetable cultivation and 34.81percent vegetable growers were unskilled regarding package of practices of vegetable cultivation. The vegetable growers gained about 81.50 percent knowledge by the treatment of training + demonstration + literature and 76.25 per cent gained skills by the treatment of training + demonstration + literature. The effect of replication (treatment) on knowledge level of the vegetable growers was higher of training + demonstration + literature (35.00%), ranked in first and the same trend was found in skills improvement. It was found that the training + demonstration + literature was the most effective treatment. The vegetable growers were found in enhancement from 5.63 per cent to 23.63 per cent after exposure of different extension methods in the category of high level of knowledge, this means 319.71 percent knowledge increased in this category. After exposure of different extension methods, the 100 percent vegetable growers were found skilled regarding vegetable production technology, i.e. nobody was unskilled after exposure of different extension methods.
Keywords: Area; knowledge; production and productivity; skill; vegetable growers